Selective laser melting of Al-3.48Cu-2.03Si-0.48Sc-0.28Zr alloy: Microstructure evolution, properties and metallurgical defects. (February 2021) - Li, Ping; Li, Ruidi; Yang, Haiou; Yuan, Tiechui; Niu, Pengda; Wang, Minbo; Li, Lanbo; Chen, Chao
Abstract: Selective laser melting (SLM) of Al-3.48Cu-2.03Si-0.48Sc-0.28Zr alloy was systematically investigated in this work, with emphasis on its microstructure evolution, mechanical properties and corresponding metallurgical defects. There is a strong correlation between SLM specimen density and laser parameters; the maximum density of 98.44% was obtained at a volumetric energy density (VED) of 166.67 J/mm 3 . The formation mechanism of pores is strongly dependent on the laser energy input and the initiation of microcracks is caused by local stress concentration. After SLM, the X-ray diffraction (XRD) peaks of as-printed specimen became broaden compared with powder due to the grain refinement and the shift of diffraction peaks to a higher value due to crystal lattice distortion of the printed specimen. The microstructure exhibits alternately column and fine grain, which is caused by the complex thermal gradient and the existence of Al3 (Sc, Zr) particles as nucleating agent. The maximum ultimate tensile strength of 329 MPa and elongation of 9.7% can be obtained at a VED of 166.67 J/mm 3 . Also, the microhardness increases with the increase of VED owing to the higher cooling rate. This study provides useful guidance for the design of high strength-ductility aluminum alloy without cracking for SLM in the future. Highlights: The Al-3.48Cu-2.03Si-0.48Sc-0.28Zr alloy was successfully printed by selective laser melting. The microstructure is composed of alternately column and fine grain. The formation mechanism of pores is strongly dependent on the energy input. The initiation of microcracks are caused by local stress concentration.